ALOX5 regulates vascular smooth muscle cells pyroptosis to affect abdominal aortic aneurysm formation - Luobo Wang; Bing Wang (Scientific Reports)
Abstract ALOX5 is a member of the lipoxygenase (LOX) family. It is ubiquitous in all tissues and cells of the human body and participates in cell metabolism, and is closely related to human inflammation and occurrence and development of various diseases. ALOX5 was reported to have a certain impact on occurrence and development of nervous system, respiratory system and cardiovascular system diseases. However, there are few reports on the effect of ALOX5 on abdominal aortic aneurysm (AAA). This study aims to clarify the relevant influence of ALOX5 on AAA occurrence or development, and explore the mechanism through which ALOX5 plays a role in AAA formation. The AAA mouse model was constructed by subcutaneous implantation of a permeable micropump and injection of angiotensin II. After different treatment, the morphology of abdominal artery was observed and photographed. The mean diameter of abdominal aorta and tumor formation rate were recorded in each group. The thickness and shape of blood vessel wall were observed by HE staining. Masson staining was used to observe distal vascular wall precipitation and vascular wall fibrosis. In the cell experiment, the level of related indexes was detected after adding angiotensin II to MA-VSMCs. The levels of inflammatory factors, ROS level, MDA level, SOD activity and LDH release were detected by ELISA. Related proteins were detected by Western blotting. ALOX5 mRNA level was assessed by RT-qPCR. Integrity of MA-VSMCs cell membrane was detected by Hoechst 33342/PI double staining kit. Ang-II induced ApoE−/− mice to establish AAA model successfully. ALOX5 expression was increased in the ApoE−/− mouse AAA model. Addition of ALOX5 inhibitor reduced the occurrence and severity of AAA as well as inflammatory, oxidative stress and pyroptotic protein levels in ApoE−/− mice. Down-regulation of ALOX5 inhibited LDH release, oxidative stress, inflammation and pyroptosis of MA-VASMCs induced by Ang II. After ALOX5 inhibition, the NF-κB pathway was inhibited. ALOX5 overexpression promoted the release of LDH, PI-positive cells, pyroptosis related protein expression, oxidative stress and inflammatory cytokine release induced by Ang II in MA-VSMCs, while they were reversed by BAY11-7082 (BAY, NF-κB inhibitors). This study confirmed that ALOX5 involved in AAA development. Adding ALOX5 inhibitors to animal modeling could delay AAA development. Silencing or overexpressing ALOX5 in MA-VSMCs induced by Ang II correspondingly decreased or increased inflammatory cytokines and pyroptosis. The addition of NF-κB pathway inhibitor BAY inhibited the increase of inflammatory factors and pyroptosis caused by ALOX5 overexpression. These results indicated that ALOX5 promoted pyroptosis through NF-κB pathway, and then promoted AAA development.